The effects of prior trading performance have on risk-taking of subsequent trading – The house money effect - LENZ TAN KOON BIN, (Institutional Knowledge at Singapore Management University, 2022)
This study tests for house money effect on 2,030 non-professional FX investors trading through an Australian Financial Service provider. The results indicate that, in general, investors display a positive relationship between prior gains and the change in subsequent weekly risk-taking - the house money effect. The results also suggest that astute investors display a stronger house money effect than mediocre investors following prior gains. In comparison, mediocre investors display a stronger disposition effect following prior losses than astute investors. The study further reveals that investors who initially demonstrated the house money effect became more prone to the disposition effect during stressful market conditions, as during the onset of the COVID-19 crisis. Concurring with Odean’s (1998) findings, the results of consequent tests demonstrate that for winners that were sold, the average excess returns holding the trade increased markedly, whilst for losing trades that were unsold, the losses escalated exponentially as the days passed. This further extends the belief that the disposition effect is detrimental to investing and that the house money effect is not as reckless as widely perceived. The house money effect is also found to be more evident in Scalpers (shorter-term traders) than Day and Swing traders (longer term traders), and the house money effect seems to dissipate over time or Scalpers are predisposed to this form of investor bias.